Scientific Opinion on Flavouring Group Evaluation 94, Revision 1 (FGE.94Rev1): Consideration of aliphatic amines and amides evaluated in an addendum to the group of aliphatic and aromatic amines and amides evaluated by the JECFA (68th meeting) - EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) (EFSA Journal)
Abstract The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids of the European Food Safety Authority was requested to consider evaluations of flavouring substances assessed since 2000 by the Joint FAO/WHO Expert Committee on Food Additives (the JECFA), and to decide whether further evaluation is necessary, as laid down in Commission Regulation (EC) No 1565/2000. The present consideration concerns a group of 12 aliphatic amines and amides evaluated by the JECFA at the 68th meeting in 2007. This revision of the consideration is made due to additional toxicity data available for two substances, N‐3, 7‐dimethyl‐2, 6‐octadienyl cyclopropylcarboxamide [FL‐no: 16.095] and N‐[(ethoxycarbonyl)methyl]‐p‐menthane‐3‐carboxamide [FL‐no: 16.111]. The substances were evaluated through a stepwise approach that integrates information on structure‐activity relationships, intake from current uses, toxicological threshold of concern and available data on metabolism and toxicity. The Panel agrees with the application of the Procedure as performed by the JECFA for 11 of the substances considered in this FGE and agrees with the JECFA conclusion, “No safety concern at estimated levels of intake as flavouring substances” based on the MSDI approach. For one substance [FL‐no: 16.090] additional toxicity data are still needed before the evaluation can be finalised. Besides the safety assessment of these flavouring substances, the specifications for the materials of commerce have also been considered and for one substance, [FL‐no: 16.090], the composition of the stereoisomeric mixture has to be specified.